Cote d'Ivoire : Evaluating Digital Payment Systems for Expanding Social Protection Coverage - World Bank (World Bank, Washington, DC, 2020)
The main objective of this technical note is to evaluate the institutional and implementation framework needed for strengthening payment systems as a core element of delivering social protection and labor (SPL) benefits to the poor, around which targeting, identification and monitoring systems operate. The assessment aims to support improving how new national programs and initiatives identify the poorest households, assess their needs and facilitate the delivery of investments and services to them by maximizing digital financial technology. The note is structured as follows. Following the introduction in section I, section II looks at institutional framework, including the regulatory environment for financial services as well as the personal identification (ID) landscape in Côte d'Ivoire. Section III assesses the current payment systems in the four focus programs chosen. Section IV provides recommendations for improvement of the payment systems of the four focus programs in the short and long term, with an eye not only toward improving service delivery for the beneficiaries of individual programs, but also toward improving coordination between programs.